Religion: Sigmund Freud's Infantile Illusions And Collective Neurosis Perspective - Susanto Susanto; Saifullah Idris (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
This paper concerns Freud's thoughts on religion. Religion is not only about faithin a great God, but also encompasses the order and discipline of life. Religioninvolves human relationships, either with God or with others. Freud saw religion asthe fulfillment of a childish desire. This can not be separated from his work as apsychologist who produced the concept of psychoanalysis and human sexual stages.Freud disputed the basis of human trust claims by giving three mutually exclusiveand holistically unsatisfactory reasons. First, we must trust without demandingproofs; Second, we must believe because our ancestors also believed; And third, wemust believe because we have evidence from ancient times. Freud contends thatsuch beliefs are nothing more than an illusion.